Efektifitas Terapi Musik Klasik Mozart dan Kangaroo Method Terhadap Peningkatan Berat Badan Pada Bayi Berat Badan Lahir Rendah (BBLR) - Siti Aminah; Ratna Wulandari (Bunda Edu-Midwifery Journal (BEMJ), 2025)
Low Birth Weight (LBW) infants are at high risk for various health complications, including growth delays. This study aims to evaluate the effectiveness of Mozart music therapy and the kangaroo method in increasing the weight of LBW infants over 30 days. The findings reveal that Mozart music therapy resulted in a weight gain of 550 grams, while the kangaroo method achieved a gain of 510 grams. These results align with previous studies showing that Mozart music therapy enhances appetite and sleep patterns in infants by regulating neurophysiological responses and reducing cortisol levels. Meanwhile, the kangaroo method improves thermal stability and promotes weight gain through direct skin-to-skin contact between mother and baby, which also increases oxytocin production. International studies confirm the effectiveness of both methods in supporting LBW infants’ growth. The combination of music therapy and the kangaroo method has been found to yield even better outcomes, with up to 20% higher weight gain compared to using either method alone. However, the implementation of these methods depends on resource availability and cultural context. This study concludes that both Mozart music therapy and the kangaroo method effectively enhance the weight of LBW infants. Combining these approaches is recommended as an optimal strategy for supporting infant growth, particularly in healthcare settings equipped with adequate technology and trained personnel.